Estratégias e lógicas envolvidas na construção da visibilidade institucional em diferentes espaços de interação na internet - Scheid, Daiane (2008)
The research has as main purpose to comprehend the logic involved in the institutional visibility construction process in the internet, from two distinct interaction spaces: an institutional portal and an Orkut community. With this purpose, the following specific objectives were established: to comprehend the visibility construction project in the internet, to identify the way which the Federal University of Santa Maria - UFSM portal is organized, and to recognize through the utilized strategies, some logics of the process through which questions regarding this institution gain visibility in this space; to identify how the biggest Orkut community about UFSM is organized and recognize through the utilized strategies, some logics of the process through which questions regarding this University gain visibility in this space. This is a qualitative research and is fundamentally interpretative. An empirical observation was done on both objects: the UFSM portal and the community in the Orkut about UFSM with the biggest number of participants. The methodology to treat these objects is based on the observation and description of how each one of the interaction spaces in the internet is organized. Moreover, three characteristics which we find to be essential on the institutional visibility construction process in these spaces were observed: type of interaction, thematic range and themes maintenance. The literature review allows to characterize the media as a visibility sphere in the contemporary days, having a crucial role on legitimating institutions. In this way, the study highlights the importance to investigate the process of media visibility construction in face of the new socio-technological possibilities, such as internet. As a communication channel in the media field, the internet builds specific models and process of interaction. In this way, it also permits a peculiar modality of institutional visibility, where questions referring to a specific institution, which is seeking for legitimation, can be displayed either by the responsible for the institutional communication or by other members, in the board or not, of the institution. The result from this proposal was the observation that the in the portal, the process of visibility construction of UFSM is characterized by a logic of linearity. On the other hand, this process in the community is constituted by logic of negotiation, dialogical.